Digital Transformation in South Korea’s Halal Market Development - Musafak Moh; Choirul Nikmah (ASEAN Journal of Halal Study, 2024)
The rapidly growing global halal industry presents both opportunities and challenges. Many countries, including those with non-Muslim majority populations, have recognized the substantial potential and benefits of participating in this market. However, the swift expansion of the halal industry does not always align with the services expected by Muslim consumers. For instance, Muslim populations in non-Muslim-majority countries, such as South Korea, often face significant challenges. The most prominent obstacles include the scarcity of mosques and the difficulty in finding halal food and determining whether market or convenience store products meet halal standards. This study examines the development of the Korean halal market through digital transformation, focusing on the experiences of the Indonesian Muslim diaspora. It employs a phenomenological approach, utilizing observations and interviews as data sources. The study also incorporates the Maqashid al-Syariah methodology to explore the issues from an Islamic legal perspective. The findings indicate that the efforts of the Indonesian Muslim diaspora to enhance the South Korean halal market through digital transformation have had a positive impact on the local Muslim community. This impact is evident in three key areas of digital development: increasing halal literacy, fostering an e-commerce-based halal market, and creating application-based halal innovations. These aspects aim to address the challenges of developing the halal market in a non-Muslim majority country while aligning with the Maqashid al-Syariah's goal of ensuring human welfare both in this world and the hereafter.